1996
DOI: 10.1021/jp952164l
|View full text |Cite
|
Sign up to set email alerts
|

Dependences of Thermal Behaviors on the Number of Layers in Langmuir−Blodgett Films of 2-Octadecyl-7,7,8,8-tetracyanoquinodimethane. 2. Annealing Effects on the Films Investigated by Atomic Force Microscopy and Ultraviolet−Visible and Infrared Spectroscopies

Abstract: The annealing effects on Langmuir-Blodgett (LB) films of 2-octadecyl-7,7,8,8-tetracyanoquinodimethane (abbreviated as octadecyl-TCNQ) have been investigated by atomic force microscopy (AFM) and ultravioletvisible (UV-vis) and infrared (IR) spectroscopies. An AFM image of a one-layer LB film of octadecyl-TCNQ scanned at room temperature shows that the film consists of numerous platelike microcrystal domains. A periodic structure of octadecyl-TCNQ molecules with a period of 0.85 nm can be observed inside these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 16 publications
2
64
0
Order By: Relevance
“…24 The SEM and AFM measurements revealed that the LB films consist of numerous platelike microcrystal domains which are superposed upon each other, like a mosaic structure (see Figure 7 of the following paper 21 ). It was also proved by the AFM measurements that these domains have periodic layered structure and well-ordered molecular arrangement.…”
Section: Thermal Behaviors Of Langmuir-blodgett Films Of 2-octadecyl-mentioning
confidence: 99%
“…24 The SEM and AFM measurements revealed that the LB films consist of numerous platelike microcrystal domains which are superposed upon each other, like a mosaic structure (see Figure 7 of the following paper 21 ). It was also proved by the AFM measurements that these domains have periodic layered structure and well-ordered molecular arrangement.…”
Section: Thermal Behaviors Of Langmuir-blodgett Films Of 2-octadecyl-mentioning
confidence: 99%
“…[21][22][23][24][25][26] In our previous papers concerning LB films of 2-octadecyl-7,7,8,8-tetracyanoquinodimethane (octadecyl-TCNQ), we reported studies on their order-disorder phase transition and annealing effects by atomic force microscopy (AFM) and ultraviolet-visible (UV-vis) and infrared (IR) spectroscopies. 24,25 These studies elucidated that phase transition temperature increases with the number of layers and that the thermal behavior of the LB films depends upon the number of layers. Moreover, it was found that the annealing effects on domain structure in the LB films of octadecyl-TCNQ are clearly different between the one-layer and multilayer films.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,8 Their corresponding AFM images validate that the hydrocarbon chains are highly ordered, well-organized, and in an interdigitated pattern inside the bilayer microcrystal plate-like domains. 5 In contrast, the CH 2 antisymmetric and symmetric stretching bands of octadecyl-TCNQ appear at 2922 and 2852 cm -1 , respectively, in the spectra of CT films. This means that the interactions among the hydrocarbon chains are weak and that, at least, the interdigitated pattern of the chains does not exist.…”
Section: Stacking Pattern Of Alkyl Chains Of Octadecyl-tcnq Moleculesmentioning
confidence: 77%
“…Its morphological feature is similar to that of the 11-layer LB film of octadecyl-TCNQ. 5 Some amorphous spots can also be found among the domains. The molecular arrangement inside the domains is different from that before the annealing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation